Strategi Alternatif untuk Keberlanjutan Ekonomi dan Peningkatan Perlindungan Lingkungan di Indonesia Mengadopsi Kerangka Pertumbuhan Hijau dan Pendalaman Keuangan - Herman Cahyo Diartho (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
The Indonesian government strives to achieve environmental sustainability and economic growth as integral components of its development strategy. Two perspectives are applied to evaluate whether Indonesia’s economic growth adversely impacts environmental preservation: the Business as Usual approach and the Green Growth framework. This study examines Indonesia’s financial commitment to green growth, which is being implemented nationwide. Employing a quantitative research approach, this study analyzes the Green Growth Framework (GGF) concerning Financial Deepening and its impact on Sustainable Development Goals from 1973 to 2014. Methodologies include the Error Correction Model (ECM) and Vector Auto Regression (VAR). The research explores the dynamics between Indonesia’s economic growth and the implementation of the GGF, highlighting how various indicators within the GGF demonstrate both immediate and long-term relationships with the framework. The analysis provides insights into the extent of Indonesia’s progress in integrating green growth principles within its financial and economic systems. The ECM and VAR methodologies reveal the short-term fluctuations and long-term trends, respectively, offering a comprehensive understanding of the interplay between economic policies and environmental sustainability. Results indicate that implementing the GGF significantly impacts financial deepening, influencing sustainable development outcomes. The findings suggest that while there is a strong connection between economic growth and environmental preservation initiatives, continuous efforts and policy adjustments are necessary to ensure the long-term success of green growth strategies. This study contributes to the broader discourse on sustainable development by presenting empirical evidence from Indonesia, serving as a potential model for other developing nations aiming to balance economic expansion with environmental stewardship. The research underscores the importance of adopting a green growth framework to achieve sustainable development goals, providing valuable implications for policymakers and stakeholders.